Estudo mecânico-quântico ab initio da propriedade fotoluminescente em compostos PbWO4, BaWO4, SrWO4 e dos processos de intercalação e difusão de Li no composto Li1+xTi2O4 - Santos, Marcos Anicete dos (2008)
Computational simulation by means of quantum-mechanical calculations is becoming an increasingly important tool in scientific research of materiaIs due the great advances in the performance of computers and in the development of more efficient algorithms, providing a deeper understanding of nanoscale mechanisms which often cannot be detected directly by the experimental measures. The development of materiaIs with efficient optical properties is of great industrial interest. The photoluminescence (PL), one important optical property, has been intensively explored in scientific optical research and in technological applications. The literature presents that the most intense PL emissions of the compounds PbWO4, Ba WO4 and SrWO4 is favored by structural disorder in its lattice. Results of computeI simulations of structurally disordered compounds PbWO4, BaWO4 and SrWO4 by means of quantum-mechanical ab initio calculations were presented in this thesis, in arder to interpret why these disordered structures favor the most intense PL emissions. The calculations indicated that these structurally disordered compounds favor intense PL emissions because contain non-homogeneous distribution of charges in its lattice causing the generation of trapped electronic boles, thus, providing electron-hole recombinations to intense and broad PL emissions. The progress of research in batteries based on lithium-ion (Li batteries) has aIso great technological importance due the commercial demand of portable devices. In particular the compound Li1+xTi2O4 (O ≤X ≤ 1) is a perspective material for application in Li batteries due to its high fatia energy storagejweight. Results of computational simulations using quantum-mechanical ab initio calculations in processes of Li intercalation and diffusion in the structure Li1+xTi2O4 (0 ≤ X ≤ 0.375) were also presented in this work, in arder to identify the most favorable migration paths of considered different concentrations, and that such identification is not experimentally possible. The calculations of the processes of Li intercalation and diffusion in the structure Li1+xTi2O4 indicate that the Li insertion is energetically favorable in alI range of concentration x studied and the Li migration are favorable only for x 2: 0.25. Quantum-mechanical calculations aIso indicate the more favorable migration paths for each concentration x considered, and that migration of lithium is more favorable in less stable local Li arrangements because the energy cost for lithium migrating in more stable arrangements is greater than the energy cost for lithium migrating in less stable arrangements.